PENERAPAN PERMAINAN MELIPAT KERTAS UNTUK MENINGKATKAN MOTORIK HALUS - Arifah, Kusnul (Universitas Islam Darul Ulum, 2016)
This research aimed to flex the fingers that will be prepared for the preparation holding a pencil. Then proceed with the paper folded to form a structure that aims to move the fingers so that it can flex its muscles and coordination. This research design was a Classroom Action Research (PTK) collaborative. The draft was conducted in two cycles. Each cycle consisted of four phases: (1) preparation of an action plan, (2) action, (3) observation, and (4) reflection. The subject was a group B of Kindergarten Bhakti Sugihwaras, Deket Lamongan, 29 children. The result showed that the learning activities of the second cycle of its development was very satisfactory. Thus, the implementation of playing folding paper could improve the fine motor skills in a group B of Kindergarten Bhakti Sugihwaras, Deket Lamongan in the academic year of 2015/2016.